Oral health inequities. Factors which determine their reality in Chile - Palomer Roggerone, Leonor (Acta Bioethica, 2016)
Although access to health care is a right in Chile, various surveys and studies show that not all Chileans have equal rates of oral health. The most deprived populations, rural, ethnic minority and older have traditionally exhibited worst results in studies. It has started to include oral health in government plans through GES coverage (Health Explicit Guarantees) of some actions or groups. Chilean Primary Health also has oral health programs in their centers. Another strategy is to promote self-care by individuals, but despite all this, the most affected groups are maintained with bad numbers. What is the cause of this disparity? Why is oral health inequitable in Chile? Survey results, publications and studies on the subject were reviewed and the resulting conclusion is that social determinants are the essential factors. Until these issues do not improve, it is difficult to achieve a fairer reality oral health.